Mechanical and physical properties of three layered particleboard from kelempayan (neolamarckia cadamba) and sawmill sawdust / Diana Julie and Nurrohana Ahmad - Julie, Diana; Ahmad, Nurrohana (2015)
The objective of this study is to determine the physical and mechanical properties of three layered particleboard from Kelempayan (Neolamarckia cadamba) and sawmill sawdust as well as to explore the effect of density and resin content on the particleboard. Sawmill sawdust is used for face and back of the particleboard, with the resin contents ( 8%, 10% and 12%) and densities ( 500 kg/m3, 600 kg/m3 and 700 kg/m3), while Kelempayan is used as the core with consistent of resin content (Urea Formaldehyde) (10%). The optimum conditions for making the particleboard was found, where mechanical properties revealed that board with higher density, 700 kg/m3 and resin content, 10%, showed the value for MOR (12.9 MPa), MOE (2001 MPa), IB (0.20 MPa) which surpassed the minimum standard for JIS A5908:2003 for board Type 13 For the physical properties, it is not pass the minimum standard because this particleboard is only suitable for interior products.